KOMODITAS DAN DINAMIKA PERDAGANGAN DI PAPUA MASA SEJARAH - M. Irfan Mahmud (Berkala Arkeologi, 2014)
There are only a few discussions about Papuaâ€™s trading in ancient history era in the context of Nusantara. This article describes the trading and its commodities in Papua, started from a foreign source about Srivijaya c. 8th century AD. Commodities from Papua became more well-known since Javaâ€™s involvement in the distribution process through â€œentrepotâ€ gate Seram Sea and Banda. Majapahit 14th centuryâ€™s records mentioned Onim as one of the important places in Papua. This paper describes the exported and imported commodities and some sites which indicated important coastal places during the dynamic of trading in historic Papua from 14th century AD onwards. From 14th to 20th century AD, beside beautiful birds, ebony and slaves, Papua also exported nutmegs, masohi (cinamomum sp.) timbers, sandalwoods, ambers, turtle shell, shark fins, pearl shells and sea cucumbers. Some commodities were also being exported later on in 20th century AD such as crocodile skins, rattan and copra. In the other hand, Papua imported many things like beads, ceramics, Timor cloth, iron tools, foods and weapons.